2015
DOI: 10.1186/s13018-015-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ceramic-on-ceramic to metal-on-polyethylene bearing surfaces in total hip arthroplasty: a meta-analysis of randomized controlled trials

Abstract: BackgroundIn recent years, the choice of ceramic-on-ceramic (COC) and metal-on-polyethylene (MOP) in primary total hip arthroplasty (THA) remains controversial. The purpose of this study was to compare the reliability and durability of COC with that of MOP bearing surfaces in THA.MethodsBased on prospective randomized controlled trials (RCTs) searched from Pubmed, Embase, Web of Science, and Cochrane central database, we performed a meta-analysis for comparing clinical and radiographic outcomes of COC with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 30 publications
2
31
0
2
Order By: Relevance
“…Previous studies have reported that COC bearings have lower risk of dislocation compared with M-PE in primary THA [11,12]. Hernigou and coworkers compared the risk of dislocation in C-PE and COC bearings implanted from 1978 to 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that COC bearings have lower risk of dislocation compared with M-PE in primary THA [11,12]. Hernigou and coworkers compared the risk of dislocation in C-PE and COC bearings implanted from 1978 to 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Bozic et al [2] in a large Medicare database of 148,827 patients undergoing THA found that MoM bearings were associated with higher risk of PJI than MoP and CoC bearings. A recent meta-analysis of five randomized clinical trials involving 897 patients with 974 hips and comparing reliability and durability of CoC (601) versus MoP (373) THAs showed that ceramic hips had decreased risks of revision for any reasons, but no difference was found between the two groups in regard to postoperative deep infection rate [7]. The total number of THAs included in the meta-analysis was relatively small considering the rate of revision for PJI is expected to be approximately 1%.…”
Section: Discussionmentioning
confidence: 99%
“…1, Gruppe 2). Die Revisionen wurden in 53 Im Gegensatz zur MoP-Gleitpaarung zeigt die CoC-Gleitpaarung einen erhöhten Abriebwiderstand, ein geringeres Taper-Korrosionsrisiko und die Fähigkeit, das Luxationsrisiko zu reduzieren [6,40,41]. Das Risiko einer Luxation ist nach Revisionseingriffen deutlich höher als in der Primärendoprothetik [2,42].…”
Section: Conclusion Modern Coc Bearings Show Advantages In Pre-unclassified